Analysis of Students’ Perceptions of Gender Awareness and Emancipation Through the Use of the Kartini Film as Learning Media in Kolisia Junior High Schools - Purwanti, Nani; Yanto; Naro, Antonius M.K (Papanda Publisher, 2026)
This study aims to analyze junior high school students’ perceptions of gender awareness and emancipation through the use of the Kartini film as a learning media. The background of this study is rooted in the limited integration of gender issues in classroom practices and the potential of visual media to bridge this gap. Using a descriptive qualitative approach, the research was conducted at Kolisia Junior High School and involved 21 seventh-grade students through observations and interviews. The Kartini film was utilized in class VII, accompanied by a brief explanation of gender concepts to support students’ understanding. The findings show that most students responded positively. They found it more engaging and easier to comprehend compared to the usual way of learning in class, such as reading or listening to explanations. The film effectively raised students’ gender awareness about the struggles faced by women in the past and inspired discussions on gender equality. However, challenges such as unfamiliar language and the film’s duration were noted by some students. Despite these obstacles, the film proved to be a meaningful tool in encouraging students to reflect on gender roles and equal rights. The study concludes that integrating films into classroom instruction can enhance students’ understanding of social issues and promote gender-sensitive education.